PROMOTING SELF-CARE AND WELL-BEING: EXPERIENCE REPORT OF ACADEMICS IN A BEAUTY WORKSHOP AT CAPS (REMUNOM, 2025)
Internships are essential in nursing education, providing practical experience and direct contact with patients. The Psychiatric Reform enabled more humane care, and Psychosocial Care Centers (CAPS) play a fundamental role in this process. This report describes the experience of nursing students in conducting a "Beauty Workshop" at CAPS Araguaia I, aimed at promoting self-esteem and well-being. The activity included haircuts, makeup, manicure, pedicure, and face painting, as well as a fashion show and bingo, encouraging patient socialization. The methodology used was participant observation, allowing students to develop active listening and empathy skills. The results showed positive impacts on patients' self-esteem and students' learning, reinforcing the importance of humanized mental health care. It is concluded that such initiatives should be encouraged, as they provide benefits for both patients and students' professional development.